Nationalsozialistische Frauenpolitik vor 1933: Dokumentation - Schade, Rosemarie (Labour / Le Travail, 1997)
The article reviews the book, "Nationalsozialistische Frauenpolitik vor 1933: Dokumentation," edited by Hans-Jurgen Arendt, Sabine Hering and Leonie Wagner.
Keywords: ARENDT, Hans-Jurgen; BOOKS -- Reviews; HERING, Sabine; NATIONAL socialism & women; NATIONALSOZIALISTISCHE Frauenpolitik vor 1933: Dokumentation (Book); Nonfiction; WAGNER, Leonie

Die unheimliche Macht des Geldes: Finanzierungsstrategien der Bürgerlichen Frauenbewegung in Deutschland zwischen 1865 und 1933 - Schade, Rosemarie (Labour / Le Travail, 1999)
The article reviews the book, "Die unheimliche Macht des Geldes: Finanzierungsstrategien der Bürgerlichen Frauenbewegung in Deutschland zwischen 1865 und 1933," by Gilla Dölle.

Frauen und Staat/Les Femmes et l'État - Schade, Rosemarie (Labour / Le Travail, 1999)
The article reviews the book, "Frauen und Staat/Les Femmes et l'État," edited by Brigitte Studer, Regina Wecker, and Beatrice Ziegler.

Clara Zetkin, féministe sans frontières - Schade, Rosemarie (Labour / Le Travail, 1994)
The article reviews the book, "Clara Zetkin, féministe sans frontières," by Gilbert Badia.
Keywords: BADIA, Gilbert; BOOKS -- Reviews; CLARA Zetkin: Feministe Sans Frontieres (Book); Nonfiction; ZETKIN, Klara, 1857-1933